Rosacea Is Characterized by a Profoundly Diminished Skin Barrier - Medgyesi, Barbara; Dajnoki, Zsolt; Béke, Gabriella; Gáspár, Krisztián; Szabó, Imre Lőrinc; Janka, Eszter Anna; Póliska, Szilárd; Hendrik, Zoltán; Méhes, Gábor; Törőcsik, Dániel; Bíró, Tamás; Kapitány, Anikó; et al. (Journal of investigative dermatology, 2020)
Rosacea is a common chronic inflammation of sebaceous gland-rich facial skin characterized by severe skin dryness, elevated pH, transepidermal water loss, and decreased hydration levels. Until now, there has been no thorough molecular analysis of permeability barrier alterations in the skin of patients with rosacea. Thus, we aimed to investigate the barrier alterations in papulopustular rosacea samples compared with healthy sebaceous gland-rich skin, using RNA sequencing analysis (n = 8). Pathway analyses by Cytoscape ClueGO revealed 15 significantly enriched pathways related to skin barrier formation. RT-PCR and immunohistochemistry were used to validate the pathway analyses. The results showed significant alterations in barrier components in papulopustular rosacea samples compared with sebaceous gland-rich skin, including the cornified envelope and intercellular lipid lamellae formation, desmosome and tight junction organizations, barrier alarmins, and antimicrobial peptides. Moreover, the barrier damage in papulopustular rosacea was unexpectedly similar to atopic dermatitis; this similarity was confirmed by immunofluorescent staining. In summary, besides the well-known dysregulation of immunological, vascular, and neurological functions, we demonstrated prominent permeability barrier alterations in papulopustular rosacea at the molecular level, which highlight the importance of barrier repair therapies for rosacea.